Construction of the scale of integration Serbian language and physical education content - Perišić Snežana P. (Baština, 2022)
The main goal of the research was to determine the psychometric characteristics of the test constructed to measure the expression of students in the final years of bachelor and master studies at the University of Niš, Faculty of Sports and Physical Education and the University of Priština - Kosovska Mitrovica, content of the subject Serbian language and physical education in the younger grades of primary school, as well as in general about integrative teaching. The research was conducted on a sample of 203 students. Descriptive techniques were used to determine the level of expression of the basic variables, while psychometric characteristics were predicted by Cronbach's alpha reliability coefficient and exploratory and confirmatory factor analysis. The scales of the created instrument show satisfying, but low reliability (Cronbach's alpha> 0.7), while the factor structure corresponds to the theoretically assumed one.